2001
DOI: 10.1002/1097-4644(20010601)81:3<499::aid-jcb1063>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the neuropeptide substance P on the rat bone marrow-derived osteogenic cells in vitro

Abstract: Substance P containing, thin, sensory nerve fibres have been demonstrated in bone and bone marrow. However the role of substance P in bone tissue is not fully understood. We investigated the effects of substance P on the growth and development of rat bone marrow-derived osteogenic cells in vitro. To examine this, the marrow-derived osteogenic cells were treated from 3rd to 6th day of subculture with substance P at concentrations 10(-10), 10(-9) and 10(-8)M. [(3)H]-thymidine, L-2,3-[(3)H]-proline incorporation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…Increased SP expression in exercised fish was shown concomitantly with induced osteogenic gene transcription and enhanced osteoid production in the osteoblasts along the amphicoel end bones and in the trabeculae. SP has previously been shown to have important roles in mineralization processes [23], osteoblast proliferation [11,12] and transcription of osteogenic marker genes [13,14]. The release of SP in bone has further been shown to directly stimulate osteoblastic bone formation in vivo [24][25][26] and to possess osteogenic effect on the formation of bone colonies and bone formation in vitro [25,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased SP expression in exercised fish was shown concomitantly with induced osteogenic gene transcription and enhanced osteoid production in the osteoblasts along the amphicoel end bones and in the trabeculae. SP has previously been shown to have important roles in mineralization processes [23], osteoblast proliferation [11,12] and transcription of osteogenic marker genes [13,14]. The release of SP in bone has further been shown to directly stimulate osteoblastic bone formation in vivo [24][25][26] and to possess osteogenic effect on the formation of bone colonies and bone formation in vitro [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…The neurotransmitter Substance P (SP) has provided promising results for both being an inducer of osteogenesis, as well as a candidate for bone regulation. SP is involved in bone mineralization [11], osteoblast proliferation [11,12] and transcription of osteogenic marker genes [13,14]. SP has further been suggested as a treatment for osteoporosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…SP neurokinin receptors are distributed in osteoblasts (Goto et al 1998), and its role in bone mineralization and osteoblast proliferation has been suggested (Adamus and Dabrowski 2001;Bjurholm 1991), particularly in regions with high osteogenic activity (Hukkanen et al 1992). Importantly, a novel observation of SP expression in chordoblasts and chordocytes has been identified in non-deformed vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical studies have shown the presence of the substance P receptor (NK1) on the plasma membrane and in the cytoplasm of osteoclasts, osteoblasts and osteocytes, and NK1 mRNA expression has been demonstrated in osteoclasts. Furthermore, substance P can increase osteoblastogenesis, inducing bone formation and protein accumulation in bone cell cultures (Bjurholm et al, 1992;Shih & Bernard, 1997;Goto et al, 1998;Adamus & Dabrowski, 2001;Offley et al;Togari, 2002). In contrast, CGRP inhibits bone resorption in vitro (Imai & Matsusue, 2002), and increases cyclic AMP (Bjurholm et al) and intracellular calcium in osteoblasts (Kawase et al, 1995).…”
Section: Discussionmentioning
confidence: 99%